(untitled) (Acta Scientiarum. Language and Culture, 2021)
Blaut-Fernandes, E. (2018). As dezenove regras do romance policial. São Paulo, SP: V. de Moura Mendonça – Livros. (Selo Demônio Negro). 86p. ISBN 978-85-66423-49-5.